2021
DOI: 10.1002/jhet.4264
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in vitro cytotoxicity, and molecular docking study of novel 3,4‐dihydroisoquinolin‐1(2H)‐one based piperlongumine analogues

Abstract: With the aim of expanding the scope of SAR on piperlongumine (PL), a naturally occurring anticancer molecule, we have designed a novel hybrid molecule bearing 3,4-dihydroisoquinolin-1(2H)-one and trans-cinnamic acids. The structure, based on hybridization strategy, is used for hybridization of naturally occurring scaffolds. We have synthesized 14 hybrid molecules by coupling 3,4-dihydroisoquinolin-1(2H)-one core with cinnamic acids using the mix anhydride approach. The newly synthesized inhibitors were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…[16][17][18][19][20][21][22][23][24][25] Interestingly, there are countless pieces of literature demonstrating compounds with anticancer activity incorporating various heterocyclic rings. 17,19,[25][26][27][28][29][30] On a similar path, we have recently reported new small molecules incorporating heterocyclic rings, imidazolidinedione, and pyrrolidinedione showing excellent antitumor activity. 19,26 Therefore, with our previous experience and knowledge, by considering the structural modification of our previously reported analogs, we developed compounds incorporating the TZD bio-isostere which is a heterocyclic ring isoxazolidinedione, to evaluate the effect of this bio-isosteric replacement over the anticancer activity of these compounds (Figure 2).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22][23][24][25] Interestingly, there are countless pieces of literature demonstrating compounds with anticancer activity incorporating various heterocyclic rings. 17,19,[25][26][27][28][29][30] On a similar path, we have recently reported new small molecules incorporating heterocyclic rings, imidazolidinedione, and pyrrolidinedione showing excellent antitumor activity. 19,26 Therefore, with our previous experience and knowledge, by considering the structural modification of our previously reported analogs, we developed compounds incorporating the TZD bio-isostere which is a heterocyclic ring isoxazolidinedione, to evaluate the effect of this bio-isosteric replacement over the anticancer activity of these compounds (Figure 2).…”
Section: Introductionmentioning
confidence: 85%
“…However, we also published compounds without the TZD nucleus showing good antiproliferative activity (Figure 1). 16–25 Interestingly, there are countless pieces of literature demonstrating compounds with anticancer activity incorporating various heterocyclic rings 17,19,25–30 . On a similar path, we have recently reported new small molecules incorporating heterocyclic rings, imidazolidinedione, and pyrrolidinedione showing excellent antitumor activity 19,26 .…”
Section: Introductionmentioning
confidence: 94%
“…Kulkarni et al proposed a series of (10a-n) PL-derivatives using 3,4-dihydroisoquinolin-1(2H)-one (DHIQ) as the primary material. [52] All derivatives have a PL-like structure with an additional benzene substitution DHIQ in place of the 5, 6-dihydropyridin-2(1H)-one found in PL (Figure 5 (<0.1 μM) showed comparatively less activity than 10g against MCF-7, indicating 10i and PL are mostly active against the rest of the breast cancer cell lines. [52] Based on thermodynamic interactions in the colchicine-binding site of tubulin and recorded GI 50 (μM), 10i was highlighted as the lead PL-based derivative among all.…”
Section: Anticancer Potency Of Proposed Pl-derivativesmentioning
confidence: 97%
“…[80] Overall, chemical modifications or structural optimisation are considered viable methods in the current drug development module for improving solubility, pharmacokinetics, bioavailability and so on. [24][25][26][52][53][54]81] However, optimistic structural modification to develop desired lead candidates is a challenging task and requires more expertise in medicinal chemistry and drug synthesis, followed by extensive experimental validation to cross the safety and regulatory profile set up in clinical trials before use in mainstream applications. Herein, the presented synthesised PL-derivatives show a higher chance of translational success in the early stages of validation, but extensive experimental investigation is required to be utilised in mainstream anticancer therapy.…”
Section: Wu Et Al Proposed Two Different Series Of Pl-derivatives Withmentioning
confidence: 99%
“…The cinnamic acid–3,4‐dihydroisoquinolin‐1(2 H )‐one hybrid 21 (IC 50 : 3.42–30 µM, MTT assay) possessed broad‐spectrum activity against MDA‐MB‐231, HeLa, C33A, DU‐145, and PC‐3 cancer cell lines and molecular docking study demonstrated that hybrid 21 could bind tightly to the colchicine domain of tubulin through a network of favorable steric and electrostatic interactions and thus act as a tubulin polymerization inhibitor. [ 51 ] The cinnamic acid–primaquine hybrids 22 and 23 could induce morphological changes in MCF‐7 cells characteristic of apoptosis and the treatment of MCF‐7 cells with hybrids 22 and 23 resulted in poly(ADP–ribose) polymerase cleavage as well as caspase‐9 activation, indicating that these hybrids induced apoptotic cell death. [ 52 ] Additionally, hybrids 22 and 23 could inhibit the migration and invasion of MCF‐7 cells.…”
Section: Cinnamic Acid Hybridsmentioning
confidence: 99%